Citizen and Technology: The Core in Developing Human-Centric Smart Cities - Berawi, Mohammed Ali; Sari, Mustika; Miraj, Perdana (UI Scholars Hub, 2024)
As urbanization continues to grow, the development of smart cities has become a pivotal strategy for addressing the complex challenges of modern urban living. These cities harness advanced technologies like the artificial intelligence (AI), Internet of Things (IoT), and Digital Twin to optimize city operations, improve sustainability, and enhance the quality of life for their residents. However, the success of smart cities should not be measured by the sheer quantity of hardware and software implemented but rather by the quality of life they create for the people who live and work within them. In other words, smart cities must prioritize human well-being as a core goal alongside technological advancement. In a smart city, hardware encompasses the physical infrastructure and devices, such as sensors, data centers, communication networks, energy grids, and other tangible components that gather data, facilitate communication, and support the city's operations. The software includes the digital systems, algorithms, and applications that process and analyze data, which facilitate decision-making, predictive analysis, and automation. However, neither hardware nor software can operate well without brainware, the human operators who oversee, maintain, and interact with these systems, as well as the citizens who utilize the smart city services offered. For a smart city to be successful, its brainware must possess the requisite knowledge, skills, and mindset to manage the technologies and adapt to their dynamic nature. It involves ensuring that city planners, public officers, and citizens are not merely passive consumers of technology but active participants who understand how to utilize the available resources to enhance their lives and communities. Smart citizens can interact with surrounding technology, which enable informed decision-making and enhancing the sustainability and governance of the city. Likewise, smart operators overseeing smart systems must have the skills to analyze data, resolve problems, and make decisions that improve the efficiency and safety of urban operations. Brainware is vital for maintaining the smart city ecosystem, since human decision-making and oversight are important for the successful integration of technology. Therefore, city operators must possess the ability to comprehend and adapt to emerging technologies and complex systems so that the seamless functioning of all smart city systems can be guaranteed. To acquire brainware, a holistic strategy in education and training is needed, which includes building technological literacy and developing critical thinking, problem-solving, and collaborative skills. Moreover, it is also essential to ensure that all citizens, irrespective of their age, background, or digital literacy, are included in the smart city ecosystem by providing equitable access to technology and information. Therefore, community participation can be encouraged and citizens’ digital literacy of citizens can be improved, which can further enable collective decision-making and responsible resources use. Consequently, the development of smart cities should not solely be limited only on the hardware and software but should also prioritize the development of brainware. We can establish cities that are not only technologically advanced but also socially inclusive by guaranteeing that the city operators are trained and that citizens are empowered to interact with the smart city technologies. A comprehensive approach that integrates hardware, software, and brainware will ensure the development of smart cities that are inclusive, resilient, and capable of safeguarding a sustainable future for urban living.